2004
DOI: 10.1093/brain/awh006
|View full text |Cite
|
Sign up to set email alerts
|

Left and right hand recognition in upper limb amputees

Abstract: Previous research suggests a close similarity in brain activity between mental simulation of a movement and its real counterpart. To explore this similarity, we aimed to assess whether imagery is affected by the loss of a limb or of its motor skills. We examined the performance of 16 adult, upper limb amputees (and age-matched controls) in a left/right hand judgement task that implicitly requires motor imagery. The experimental group included subjects who had suffered the amputation of the dominant or the non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
180
3
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(203 citation statements)
references
References 34 publications
13
180
3
2
Order By: Relevance
“…This last point is compatible with less extreme handedness scores in our left-handed participants (if compared to the right-handed participants) and the observation that right handers processed right stimuli (hands and feet) faster than left stimuli. Faster RTs for mental rotation of right body parts with respect to left body parts has been reported by several studies involving right-handed healthy participants (Parsons 1987;Gentilucci et al 1998;Ionta et al 2007;Funk and Brugger 2008), upper limb amputees (Nico et al 2004) and congenital amputees (Brugger et al 2000), suggesting that right handers are generally faster with right body parts. Our data support these previous Wndings and also extend them by showing that left-handed participants did not show either laterality preference and indicating that mental rotation of body parts depends at least on motor (and/or proprioceptive) and visual mechanisms that seem to interact diVerently in right-and left-handed people.…”
Section: Posturementioning
confidence: 50%
“…This last point is compatible with less extreme handedness scores in our left-handed participants (if compared to the right-handed participants) and the observation that right handers processed right stimuli (hands and feet) faster than left stimuli. Faster RTs for mental rotation of right body parts with respect to left body parts has been reported by several studies involving right-handed healthy participants (Parsons 1987;Gentilucci et al 1998;Ionta et al 2007;Funk and Brugger 2008), upper limb amputees (Nico et al 2004) and congenital amputees (Brugger et al 2000), suggesting that right handers are generally faster with right body parts. Our data support these previous Wndings and also extend them by showing that left-handed participants did not show either laterality preference and indicating that mental rotation of body parts depends at least on motor (and/or proprioceptive) and visual mechanisms that seem to interact diVerently in right-and left-handed people.…”
Section: Posturementioning
confidence: 50%
“…It has been demonstrated, for example, that patients suffering from chronic arm pain (Schwoebel et al 2001) or from complex regional pain syndrome (Moseley 2004) show a specific impairment in the mental rotation of the body part affected by pain. Moreover, a study in upper limb amputees showed that judging the laterality of body parts was more difficult in patients with amputation of dominant than non dominant limb (Nico et al 2004). The close relationship between actual sensorimotor disturbance and mental rotation deficits has been suggested also by a study in patients with focal hand dystonia, a neurological disease characterised by sustained muscular contractions localized to the dominant hand (Fiorio et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…However comparing the performances for left and right stimuli rotated of the same degree, the stimuli which presented the black patch on the right side were identified in most of the cases faster than the stimuli that had the patch on the left side. It is important to note that most studies on mental rotation, including the present one, recruited only right-handed subjects and found faster responses for right stimuli with respect to left ones both in healthy participants [19,22,25,30], and clinical patients [3,29]. The righthanders' preference for right stimuli is also consistent with a recent study that systematically investigated the preference for the "right" stimuli, demonstrating that the effect of laterality is preserved for right-handers (all subjects in the current study were right-handed) but not left-handers [26].…”
Section: Discussionmentioning
confidence: 64%
“…Moreover, mental rotation of body parts seems to be influenced by both central and peripheral factors. Indeed it can be impaired by transcranial magnetic stimulation applied over the primary motor cortex of healthy subjects [21], by cortical [43] and subcortical [24] lesions, as well as in patients with upper limb amputation [29], locked-in syndrome [6], chronic upper limb pain [37] and Parkinson's disease [15]. In addition, patients with idiopathic cervical dystonia show an impairment in the mental rotation of body parts but not for non-body parts, such as cars [18], suggesting the dissociation between the mental manipulation of body and non-body parts [6].…”
Section: Introductionmentioning
confidence: 99%